Development of A Web-Based Information System for Material Inventory Control: The Case of An Automotive Company - Renjana Setyoandara Wibisono; Tanika D Sofianti; Setijo Awibowo (Bina Nusantara University, 2016)
Inventory control is controlling the materials movement to fulfill the requirements. The materials can from the direct and indirect materials. the indirect materials are the materials that cannot be calculated according to the bill of materials. Indirect materials need safety stocks, so the requirements can always be fulfilled, means it need the control and monitoring of their levels. To control the movement of the materials, each department have roles to control and information that need to be shared. PT XYZ is an automotive assembler company, the company need a tool to control the indirect materials inbound and outbound and control its stock. This research is to have the tool that will be a web-based program because to share the information throughout the department of planning, production, and logistics. In developing and implementing the program itself, the RUP methodology is used to guide in doing this research with having four phases and activities that support the research. The result is the program itself have been successful to fulfilled the user requirements. The program shows the real time information for the levels of the materials and also the inbound and outbound of the materials for the user to monitor its levels.